Cellular Responses to Stress - Downes, C. P. (Book collections on Project MUSE., 2014)
Cellular Responses to Stress brings together a group of scientists who work on different but interrelated aspects of cellular stress responses. The book provides state-of-the-art information on the wide spectrum of ways in which cells can respond to different forms of stress induced by chemicals, oxidants, and DNA-damaging agents. Mechanisms are described that involve altered uptake and efflux of chemical agents, intracellular detoxification, and DNA damage responses. Many of these changes trigger a cascade of reactions mediated by stress-activated signaling pathways, which have the.